(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2026)
Taboo is an inhibition or general agreement based on socio-cultural custom to prevent feeling and emotion from doing or talking about something that is being found sacred or offensive. It is a social or religious custom prohibiting or restricting a particular practice or forbidding association with a particular person, place, or thing. Taboos are common to different groups to restricting a particular practice, but the reasons for such may be quite different from one set of group to another. However, the Yoruba ethnic group of south western Nigeria, which is the focus of this work, has a lot of cultural practices which are so valued despite the westernization by the European colonialist. These cultural practices were introduced by the founding father of this ethnic group and are meant to regulate the moral order of the society. Therefore, this paper sets to give an insight into different forms of taboos among the Yoruba and how are these taboos acting as a propelling force in preserving Yoruba cultural beliefs for future generations. It will also delve into means and ways of entrenching acceptable moral order and values into Yoruba society through the use of taboos. To achieve these, historical and exploratory methods will be employed as the tools of work in the course of this research work.